Nomenclature of the Balkan alliance Romuleion graecae (Poetea bulbosae) - Terzi, Massimo; Jasprica, Nenad; Čarni, Andraž; Matevski, Vlado; Bergmeier, Erwin; Theurillat, Jean-Paul (Acta Botanica Croatica, 2024)
The Romuleion, the only alliance of the order Poetalia bulbosae (class Poetea bulbosae) found on the Balkan Peninsula, represents Mediterranean perennial and ephemeral pastures. It has been found in several Balkan countries, from Greece to the Republic of North Macedonia, Montenegro, Croatia and Bulgaria. However, a revision of its nomenclature according to the fourth edition of the International Code of Phytosociological Nomenclature shows that the name of the alliance was not validly published. In this paper we therefore describe the new alliance Romuleion graecae, together with the new association Plantagini lagopodis-Poetum bulbosae.